1996
DOI: 10.1212/wnl.47.3.626
|View full text |Cite
|
Sign up to set email alerts
|

Reversible parkinsonism and cognitive impairment with chronic valproate use

Abstract: Following our initial report of the insidious development of reversible, valproate-induced hearing, motor, and cognitive dysfunction in two patients, we evaluated 36 patients in an epilepsy clinic who had been taking therapeutic levels of valproate for at least 12 months; 29 of these patients were examined according to a prospective protocol. We observed varying degrees of parkinsonism and cognitive impairment, from none to severe. Discontinuation of valproate in 32 affected patients led to subjective and obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
2
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 7 publications
0
72
2
4
Order By: Relevance
“…A total of 72% improved after discontinuing VPA. 26 Since patients with AD are likely sensitive to other neurotoxic insults 27,28 it is possible that the same potentially neurotoxic effects of divalproex associated with brain volume loss in the first 12 months of this longitudinal study also caused the initial rapid decline in MMSE scores observed here. Notably, analysis of adverse events and laboratory data from the primary ADCS divalproex treatment trial showed no evidence of significant neurotoxicity in any participants during the 24-month study.…”
Section: Discussionmentioning
confidence: 84%
“…A total of 72% improved after discontinuing VPA. 26 Since patients with AD are likely sensitive to other neurotoxic insults 27,28 it is possible that the same potentially neurotoxic effects of divalproex associated with brain volume loss in the first 12 months of this longitudinal study also caused the initial rapid decline in MMSE scores observed here. Notably, analysis of adverse events and laboratory data from the primary ADCS divalproex treatment trial showed no evidence of significant neurotoxicity in any participants during the 24-month study.…”
Section: Discussionmentioning
confidence: 84%
“…First, cognitive functioning and behavior showed a striking improvement within a few days of reducing VPA dosage, and a repeat MRI performed 5 months after drug discontinuation revealed disappearance of pseudoatrophic changes. Second, an association of VPA with reversible severe cognitive deterioration and pseudoatrophy of the brain has recently been suggested in other patients (5,(7)(8)(9)(10). The possibility that pseudoatrophic changes may be related to LTG comedication cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of normal background EEG activity may be helpful in differentiating this condition from other disorders possibly associated with brain atrophy, even though in the syndrome of reversible dementia associated with parkinsonism a slowing in background EEG activity has been reported (5). Other conditions to be considered for differential diagnosis include VPAinduced stupor (2,13,14) with or without hyperammonemia (3,14), which can be differentiated because of lack of brain atrophy (unless preexistent), impairment of consciousness and, in some stuporous cases, clinical or EEG evidence of increased seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…Valproate can worsen Parkinsonism and cause cognitive deterioration. Both side effects are reversible upon drug discontinuation [Armon et al 1996]. Zonisamide (25-200 mg/day) has been studied in 15 patients with PG, HS, CE or CS in a noncontrolled and open-label design.…”
Section: Management Of Impulse Control Disordersmentioning
confidence: 99%